Safety of a feed additive consisting of a dried aqueous ethanol extract from the leaves of Melissa officinalis L. for all animal species (Nor‐Feed SAS) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) (Wiley, 2021)
Abstract The additive under assessment is a dried aqueous ethanol extract of Melissa officinalis L. leaves, intended to be used as a sensory additive (flavouring compound) in feed for all animal species. The aqueous ethanol extract is specified to contain ≥ 10% of hydroxycinnamic acid derivatives including ≥ 3% of rosmarinic acid. In a previous assessment, considering the contradictory data from the Ames tests and uncertainty about the qualitative and quantitative presence of flavonoids and other compounds in the extract from M. officinalis L. leaves, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) could not conclude on the safety of the additive at the proposed use levels of up to 100 mg/kg complete feed for the target species, the consumer and the user. The new data submitted identified luteolin 3′‐glucuronide as the only flavonoid present in the additive, improved the characterisation of the hydroxycinnamates present and demonstrated that the additive is not genotoxic. The FEEDAP Panel concludes that the additive under assessment is safe up to the maximum proposed use level of 100 mg/kg complete feed for all animal species. The use in water for drinking is safe provided that the total daily intake of the additive does not exceed the daily amount that is considered safe when consumed via feed. No safety concern would arise for the consumer from the use of the additive up to the highest safe level in animal nutrition. The exposure of users to dusts from the additive is not of concern. No data are provided on irritant properties for eyes or skin, thus no conclusion can be drawn on these aspects. Due to the nature of the additive, it may be assumed to be potentially both a skin and respiratory sensitiser.